Voting power in the proxy process - Bhagat, Sanjai; Jefferis, Richard H. (Journal of Financial Economics, 1991)
The likelihood that a firm will enact a management-sponsored antitakeover charter amendment depends on ownership structure. This implies that the adoption of antitakeover amendments may be anticipated. Then announcement returns provide a biased estimate of wealth effects. An estimator that corrects for the bias induced by anticipation indicates that the enactment of an antitakeover amendment is associated with a statistically significant decrease in shareholder wealth. The voting power of employee stock ownership plans and the chief executive officer plays a prominent role in determining whether a firm will adopt this type of takeover defense.